2015
DOI: 10.7287/peerj.preprints.1564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of b-type cytochromes in prokaryotes

Abstract: Abstract:Prokaryotes use a wide variety of bioenergetic pathways but the order of emergence of these pathways and their evolutionary relationships are still unresolved issues. In this study we focus on the evolutionary relationships of different families of b-type cytochromes, which form part of a variety of bioenergetic enzymes (the cytochrome b 6 f complex, ubiquinol and menaquinol reductases, formate dehydrogenase, Ni/Fehydrogenase, and succinate dehydrogenase). We use data from 272 species of fully sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Microbial ETCs demonstrate ecological coherence of terminal oxidases such as cytochrome bd, and A-, B-and C-type hemecopper cytochrome families at certain taxonomic ranks (BrochierArmanet et al, 2009;Koumandou and Kossida, 2015). For example, genome comparisons across Proteobacterial classes suggest that the presence of A-type heme copper cytochromes is more widely distributed across Gamma (130/157 genomes), Beta (48/53 genomes) and Alpha-Proteobacteria (79/83 genomes) than EpsilonProteobacteria (0/19) (Brochier-Armanet et al, 2009).…”
Section: Physiological Differences In Electron Transport Chainsmentioning
confidence: 99%
“…Microbial ETCs demonstrate ecological coherence of terminal oxidases such as cytochrome bd, and A-, B-and C-type hemecopper cytochrome families at certain taxonomic ranks (BrochierArmanet et al, 2009;Koumandou and Kossida, 2015). For example, genome comparisons across Proteobacterial classes suggest that the presence of A-type heme copper cytochromes is more widely distributed across Gamma (130/157 genomes), Beta (48/53 genomes) and Alpha-Proteobacteria (79/83 genomes) than EpsilonProteobacteria (0/19) (Brochier-Armanet et al, 2009).…”
Section: Physiological Differences In Electron Transport Chainsmentioning
confidence: 99%
“…Koumandou and co-workers mapped the distribution of nine bioenergetic modes using 16S rRNA (more later) sequences from 272 species of fully sequenced prokaryotes, which represented the full diversity of prokaryotic ancestries. They reported that there was an irregular distribution of metabolic pathways among different lineages due to gene transfer events and an ancient origin and diversification of b-type cytochromes, which means that bioenergetic pathways were dynamic amid the human gut microbial community [19][20][21].…”
Section: Horizontal Gene Transfermentioning
confidence: 99%